CT of coronary heart disease: part 1, CT of myocardial infarction, ischemia, and viability - Vliegenthart, Rozemarijn; Henzler, Thomas (American journal of roentgenology, 2012)
CT Technology and Techniq...CT of Myocardial Infarcti...CT of Myocardial Ischemia...CT of Myocardial Viabilit...CT of Myocardial Infarcti...ReferencesCITING ARTICLES OBJECTIVE. This article reviews the CT-based approaches aimed at the assessment of myocardial infarction, ischemia, and viability described in the recent literature. CONCLUSION. Rapid advances in CT technology not only have improved visualization of coronary arteries but also increasingly enable noncoronary myocardial applications, including analysis of wall motion and the state of the myocardial blood supply. These advancements hold promise for eventually accomplishing the goal of comprehensively evaluating coronary heart disease with a single noninvasive modality.
Gesehen am 09.10.2018